Dissolved recycled expanded polystyrene as partial replacement in plaster composites. (15th April 2023) - Zaragoza-Benzal, Alicia; Ferrández, Daniel; Atanes-Sánchez, Evangelina; Saíz, Pablo
Abstract: The recovery of Construction and Demolition Waste (CDW) for its reincorporation into the manufacturing process of new materials is fundamental in the fight against environmental pollution, reducing the current high consumption of raw materials and boosting energy savings. The aim of this research is the study and development of a new plaster-based material in which the conglomerating material is partially replaced by dissolved recycled expanded polystyrene. In the experimental campaign, different dosages have been used in which the plaster material has been progressively replaced by the dissolved recycled expanded polystyrene, in order to subsequently carry out a physicochemical, physical and mechanical characterisation of the composites. The results obtained show how the incorporation of expanded polystyrene in solution as a partial replacement of the binder generates a homogeneous plaster composite, favouring the total integration of the waste in the matrix of the construction material finally produced. It has been observed that this new material has, in comparison with traditional plasters, a very low density, high thermal resistance and excellent plate bending behaviour. These properties position the developed material as a viable alternative in the production of more sustainable prefabricated plates and panels through the application of circular economy criteria. Highlights: Incorporation of EPS waste solution as a partial replacement for plaster contributes reducing the use of natural resources. The addition generates a homogeneous material by fully integrating the waste into the binder matrix. Addition of EPS solution reduces the specific weight of the new material, as well as its thermal conductivity. The new material developed showed an excellent flexural behaviour in plates.